The relationship between leadership behaviour and job satisfaction among employees in GIATMARA Malaysia / Zam Azima Zamri - Zamri, Zam Azima (2014)
The purpose of this study was to identify the relationship between leadership behaviour and job satisfaction perceived by employees at GIATMARA Malaysia headquartering in Kuala Lumpur. In this descriptive study, the quantitative method was chosen and the data was collected using questionnaire. The questionnaires were randomly distributed to the 160 employees in 13 departments at GIATMARA Malaysia and only 106 usable survey instruments were usable for analyses. The result from the study revealed that the Head of Departments in GIATMARA Malaysia indicated initiating structure was the types of leadership behavior and the job satisfaction was at high level as perceived by the employees. The satisfaction of the employees in GIATMARA Malaysia was influenced by intrinsic factors. This study indicated that the demographic variables did not indicated any significant difference with job satisfaction among the employees. The study also did confirm that there was a moderate and significant relationship between job satisfaction towards consideration and initiating structure at GIATMARA Malaysia. Based on the finding revealed, the implications for practices were provided in this study. The recommendations for the improvement of practices suggested to GIATMARA Malaysia to provide leadership training and recognition to the employees. Recommendation for future study also provided as future researcher can using larger population, different sample or using mixed methods as to study about relationship between leadership behavior and job satisfaction.